2004
DOI: 10.1590/s1516-89132004000200019
|View full text |Cite
|
Sign up to set email alerts
|

Alpha amylase from a fungal culture grown on oil cakes and its properties

Abstract: Solid-state fermentation was carried out for the production of alpha-amylase using Aspergillus oryzae. Different oil cakes such as coconut oil cake (COC) sesame oil cake (SOC), groundnut oil cake (GOC), palm kernel cake (PKC) and olive oil cake (OOC) were screened to be used as substrate for the enzyme production and also compared with wheat bran (WB). GOC was found to be the best producer of the enzyme among these. Combination of WB and GOC (1:1) resulted higher enzyme titres than the individual substrates. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 15 publications
3
33
0
9
Order By: Relevance
“…None of the metal ions evaluated was required for the activity of amylase from the Rhizobium strain ( (Pandey et al, 2000;Gupta et al, 2003;Ramachandran et al, 2004); in contrast, Chakraborty et al (2000) reported an amylase from Bacillus stearothermophilus whose activity was inhibited by divalent metal ions. Inhibition or no effect in the presence of some mono and trivalent cations (1 mM, 5 mM, 10 mM or 50 mM) were also documented for amylases from Lactobacillus manihotivorans LMG 18010T (Aguilar et al, 2000), Bacillus amyloliquefaciens (Sarikaya and Gürgün, 2000), Bacillus sp.…”
Section: Effect Of Metal Ions On Amylase Activitymentioning
confidence: 99%
“…None of the metal ions evaluated was required for the activity of amylase from the Rhizobium strain ( (Pandey et al, 2000;Gupta et al, 2003;Ramachandran et al, 2004); in contrast, Chakraborty et al (2000) reported an amylase from Bacillus stearothermophilus whose activity was inhibited by divalent metal ions. Inhibition or no effect in the presence of some mono and trivalent cations (1 mM, 5 mM, 10 mM or 50 mM) were also documented for amylases from Lactobacillus manihotivorans LMG 18010T (Aguilar et al, 2000), Bacillus amyloliquefaciens (Sarikaya and Gürgün, 2000), Bacillus sp.…”
Section: Effect Of Metal Ions On Amylase Activitymentioning
confidence: 99%
“…These results are in agreement with results reported by Adejuwon et al (2015), who reported an optimal temperature of amylase production to be 30 0 C for Rhizopus arrhizus. Many workers have also reported that 30 0 C was the optimum temperature for amylase production by several fungal genera and species including Aspergillus flavus (Mukherjee and Majumdar, 1973), Penicilium fellutanum (Ramachandran et al, 2004), Aspergillus sp. JGI 12 (Alva, et al, 2007), Aspergillus niger (Bhattacharya et al, 2012;Dalal et al, 2014Ogbonna et.…”
Section: ] Effect Of Different Culture Media On Amylase Productionmentioning
confidence: 99%
“…They are very extensively used in beverages, baby foods and pharmaceutical industries. Besides their use in starch saccharification, they also find application in brewing, paper and distillery industries (Ramachandran et al, 2004).…”
Section: Introductionmentioning
confidence: 99%